Valuing Health Damage from Polluting Energies in Benin - BASSONGUI, Nassibou; HONLONKOU, N'lédji Albert (My University, 2023)
This research assesses the health consequences of indoor air pollution resulting from the use of polluting cooking energies in Benin, employing a nationally representative household dataset. Using the health production function approach, we cal- culated both direct costs (related to medical expenses) and indirect costs (linked to income loss) based on a structural model that accounts for averting behaviours and household heterogeneity. Our findings reveal that reliance on polluting cooking energies significantly increases the risk of illness, particularly respiratory infections and cardiovascular diseases. Notably, the economic costs associated with these dirty cooking energies outweigh the direct medical costs. These results underscore the urgency of promoting clean cooking alternatives in Benin. The estimated health damage can serve to raise awareness among households about the risks of using polluting cooking energies. Furthermore, the estimated costs can provide insights into households' willingness to invest in a transition from polluting to clean cooking energies, potentially informing targeted energy transition policies.
Keywords: Polluting cooking energy · Health damage · Economic valuation